The immune response to COVID-19: Does sex matter? - Ho, Jim Q; Sepand, Mohammad Reza; Bigdelou, Banafsheh; Shekarian, Tala; Esfandyarpour, Rahim; Chauhan, Prashant; Serpooshan, Vahid; Beura, Lalit K; Hutter, Gregor; Zanganeh, Steven (Immunology, 2022)
The coronavirus disease 2019 (COVID-19) pandemic has created unprecedented challenges worldwide. Severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) causes COVID-19 and has a complex interaction with the immune system, including growing evidence of sex-specific differences in the immune response. Sex-disaggregated analyses of epidemiological data indicate that males experience more severe symptoms and suffer higher mortality from COVID-19 than females. Many behavioural risk factors and biological factors may contribute to the different immune response. This review examines the immune response to SARS-CoV-2 infection in the context of sex, with emphasis on potential biological mechanisms explaining differences in clinical outcomes. Understanding sex differences in the pathophysiology of SARS-CoV-2 infection will help promote the development of specific strategies to manage the disease.
Keywords: pandemie; immune system; imunita; Immunity; lidé; Risk Factors; Sex Factors; sex; Female; Pandemics; COVID-19; Male; ženské pohlaví; sexuální faktory; Humans; mužské pohlaví; SARS-CoV-2; sex hormones; rizikové faktory; gender